The Influence of the Living Values Education (LVE) Approach on Increasing Religious Moderation of PAI (Islamic Education) Teachers in Pekanbaru Indonesia - Rosidi, Imron; Soim, Muhammad; Arbi, Arbi; Kasmuri, Kasmuri (Lembaga penelitian dan pengabdian kepada masyrakat, 2024)
Indonesian society has long been known to have an open and moderate religious character as the process of Islamization taking place in peaceful Indonesia. However, recently there has been a trend towards a